A case report of tubular apocrine adenoma of lower eyelid - Michele Altieri; F Giacomelli; L Anselmi (Journal of Surgery and Surgical Research - Peertechz Publications, 2023)
Moll glands are sweat apocrine glands close to the eyelid margin. Tumors derived from Moll glands are rare, although Moll glands cysts are frequent. They originate from their glandular tissue or tubules. In this report we present a rare case of a lower eyelid skin tubular apocrine adenoma occurred in the right eye lower eyelid of a caucasian 45 year old woman. The lesion was nodular and dome shaped and its size was 1.5 × 3.5 × 2 mm. After a complete excision the lesion was analyzed by our pathology unit.  Histologic sections were stained with haematoxylin and eosin, alcian blue, periodic acid-Schiff (PAS). Additionally, the following immunohistochemical markers were used: cytokeratin 7 (CK7), cytokeratin 8/18 (CK8/18), cytokeratin 20 (CK20), S-100 protein and gross cystic disease protein 15 (GCDFP-15) (4,5). The immunohistochemical and phenotypic features resulted suggest the diagnosis of lower eyelid tubular apocrine adenoma probably originated from Moll glands. These findings allowed us to diagnose a very rare and benign cutaneous lesion of eyelid skin.